Not too dry, not too wet - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Mycotoxins in grain CTA, GASGA, 1997. 12 pp. CTA number 812. 5 credit points